Study on the Efficiency of Biomedical and Degradation of Dye through CuO Nanoparticles Synthesized at Various Molar Concentrations - B. Arunkumar; S. Johnson Jeyakumar; M. Jothibas (Progress in Chemical Science Research Vol. 8, 2023)
CuO nanoparticles synthesized by different molarities like 0.1, 0.2 and 0.3M at calcinations temperature 500oC. The CuO is heavily convertible metal oxide by its attractive properties. The XRD analysis revealed significant peaks related to the monocrystalline nature of CuO nanoparticles, and the average crystalline size of CuO nanoparticles is smaller as the molarities increase (23-19 nm). CuO nanoparticles may be seen in the SEM image to be well distributed, well linked, and compatible with the crystal system. There was a high cultural character. The blue shift in the absorption spectrum can be due to the CuO nanostructures’ tiny size. CuO nanoparticles in the monoclinic phase are identified by FTIR spectra as having a band of characteristics with high intensity broad band peaks at 496.96 cm-1. The synthesis of CuO nanoparticles was calcined temperature at 500°C, the particle size of the nanoparticles was found to be in the range of 23–19 nm. These sizes of integrated CuO NPs is a cost-efficient, biological molecule capable of working with antibiotics against gram positive and gram negative bacteria’s like Staphylococcus saprophyticus, Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli.